Upaya Komersialisasi IRT Karya Tani Pontianak melalui Pendampingan Manajemen Tanaman Perilla (Tanaman Shiso) - Steven, Steven; Barata, Juliahir; Sapira, Mokalistiani; Jesichapramanda, Jesichapramanda (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
Perilla plant (shiso plant) is still very foreign and rarely heard of by Indonesian people, but in Asian countries, especially Japan and Korea, the perilla plant has become an addition to food, especially perilla leaves which have a distinctive taste and have become an addition to side dishes in Japan and Korea. In Korea the fresh leaves of the plant can be used as fresh vegetables for Korean barbecue. The STIE Indonesia Pontianak PKM team saw an opportunity from this perilla plant, so the STIE Indonesia PKM team gathered housewives who had free time, wanted to gain knowledge and earn a little income. The IRT Karya Tani group has been formed for approximately 6 months and has started planting perilla plants starting from seed and is still in the process of growing these perilla plants. Based on this condition and awareness of applying knowledge to the community, the PKM Implementation Team always provides development and training to get to know this perilla plant first so that in the future it can be used as a commercialization business. The aim of this activity is that the perilla plant can grow and be used for commercialization.